Visualization representing benefits of pre-requirement specification traceability - Altaf, Sohaib; Shah, Asadullah; Imtiaz Ali, Najma; Shah, Abdul Salam; Ahmed, Syed Faiz (Science Publishing Corporation Inc, 2018)
Representation of Pre-RST information is very useful using visualized elements for realization of benefits of requirement traceability. This improves the practitioner motivation to maintain Pre-RST information during life cycle processes. Few researchers proposed visualization for Post-RST due to which many benefits of requirement traceability cannot be realized. This paper proposed an improved visualization representing Pre-RST information that demonstrates various benefit of requirement traceability. In order to evaluate empirically, an experiment is conducted and textual representation of traceability information is obtained. In order to strengthen our claim a survey is conducted to compare textual representation of traceability information with proposed visualization and results are compiled.